Right ventricular mechanics among beta-thalassemia major patients. (3rd October 2022) - Patsourakos, D; Aggeli, C; Gatzoulis, K; Delicou, S; Xydaki, A; Koukos, M; Gialleli, F; Dimitroglou, Y; Tsioufis, K
Abstract: Introduction: Right ventricular function among β-thalassemia (β-TM) patients is affected by both pulmonary circulation pressure and primary iron deposition on right ventricular myocardium. Purpose: In our study we aimed to detect the presence of impaired right ventricular function and right ventricle to pulmonary circulation (RV-PC) coupling by applying novel echocardiographic techniques among these patients. Methods: 47 β-TM patients (mean age 39.02±8.76 years, 48.9% male sex) and 24, age and sex matched, healthy controls were examined by transthoracic echocardiography. Conventional echocardiographic parameters were estimated (LVEF, E/e' ratio, left atrial volume index (LAVI), right ventricular systolic pressure (RVSP), S' wave of tricuspid annulus), alongside with deformation indices (left atrial strain at reservoir phase (LASr), right ventricular free wall (RVfw) and 4 chamber (RV4c) strain), as well as RV-PC coupling expressed as S'/RVSP, RVfw/RVSP and RV4c/RVSP. T2* was calculated by cardiac magnetic resonance imaging in β-TM patient group. Results: E/e' ratio, LVEF, LAVI, RVSP, LASr, RVfw, RV4c, S'/RVSP, RVfw/RVSP and RV4c/RVSP differed significantly between patients and controls (Table 1). T2* did not correlate with either right ventricular deformation indices or RV-PC coupling indices. A correlation was found regarding LASr with both S'/RVSP (r=0.383, p=0.008) and RV4c/RVSP (r=−0.388, p=0.007) but not with RVfw/PVSP (Table 2). Conclusions: Right ventricular deformation indices were found to be impaired in β-TM patients compared to controls, but they do not seem to be associated with myocardial iron load (T2* index). RV-PC coupling was also found to be impaired among patients and a correlation was found between RV-PC indices and left atrial strain. The latter suggests that the presence of atrial cardiomyopathy in β-TM patients could be associated with the impaired RV-PC coupling. Funding Acknowledgement: Type of funding sources: None.